Exposing the Barcoding Void: An Integrative Approach to Study Snail-Borne Parasites in a One Health Context - Schols, Ruben; Mudavanhu, Aspire; Carolus, Hans; Hammoud, Cyril; Muzarabani, Kudzai C.; Barson, Maxwell; Huyse, Tine (Frontiers in Veterinary Science, 2020)
Trematodes are snail-borne parasites of major zoonotic importance that infect millions of people and animals worldwide and frequently hybridize with closely related species. Therefore, it is desirable to study trematodiases in a One Health framework, where human and animal trematodes are considered equally important. It is within this framework that we set out to study the snail and trematode communities in four artificial lakes and an abattoir in Zimbabwe. Trematode infections in snails were detected through multiplex PCR protocols. Subsequently, we identified snails by sequencing a partial mitochondrial cytochrome c oxidase subunit I (COI) fragment, and trematodes (adults from the abattoir and larval stages detected in snails) using COI and nuclear rDNA markers. Of the 1,674 collected snails, 699 were molecularly analyzed, in which we identified 12 snail and 19 trematode species. Additionally, three parasite species were sampled from the abattoir. Merely four trematode species were identified to species level through COI-based barcoding; identification of members of the superfamilies Opisthorchioidea and Plagiorchioidea required a phylogenetic inference using the highly conserved 18S rDNA marker, as no related COI reference sequences were present in public databases. These barcoding challenges demonstrate a severe barcoding void in public databases, which can be attributed to the neglected status of trematodiases. Adding to this, many available sequences cannot be used as different studies use different markers. To fill this gap, more studies on African trematodes, using a standardized COI barcoding region, are desperately needed.